Finite-time stability analysis of impulsive discrete-time switched systems with nonlinear perturbation - Wang, Yijing; Shi, Xiaomeng; Zuo, Zhiqiang; Liu, Yuhua; Chen, Michael Z.Q. (International journal of control, 2014)
The problem of finite-time stability for a class of discrete-time switched systems in the presence of both non-Lipschitz perturbation and impulse effects is studied in this paper. Based on the average dwell-time approach, a criterion is proposed which ensures that the system's state trajectory remains in a bounded region of the state space over a pre-specified finite-time interval if we impose a bound on the initial condition. It is shown that the finite-time stability degree could be greater than one, which is quite different from the existing results for asymptotic stability. Moreover, the total activation time of the Schur stable subsystems does not need to be greater than that of the unstable subsystems. A numerical example is presented to illustrate the effectiveness of the proposed design method.